ESICM consensus-based recommendations for the management of very old patients in intensive care - Beil, Michael; Alberto, Laura; Bourne, Richard S; Brummel, Nathan E; de Groot, Bas; de Lange, Dylan W; Elbers, Paul; Emmelot-Vonk, Marielle; Flaatten, Hans; Freund, Yonathan; Galazzi, Alessandro; Garcia-Martinez, Ana; et al. (Intensive care medicine, 2025)
PURPOSE: The heterogeneity of very old patients (age ≥ 80 years) and the prevalence of complex geriatric syndromes in this cohort constitute major challenges for the classical methods of evidence-based medicine to inform clinical practice. The lack of robust guidance for the management of critical conditions in these patients contributes to considerable uncertainty among practitioners and unwarranted variations of care. The European Society of Intensive Care Medicine (ESICM) initiated a Delphi study to translate the empirical knowledge of experts in this field into consensus-based recommendations for clinical practice. METHODS: A multi-national group of specialists in intensive care, emergency, and geriatric medicine provided opinions on managing very old patients with critical conditions. Strong or moderate consensus was defined as having at least 90% or 80% of experts, respectively, expressing agreement or disagreement on the three highest or lowest levels of a 9-points Likert scale. RESULTS: Twenty-eight members of the expert steering group and 82 additional experts completed two Delphi rounds. After discussing the results, the steering group issued recommendations for 48 statements and 2 checklists for which consensus was achieved. In addition to determining fundamental principles, they include advice on goals of care and the decision-making about admission to and treatment of patients in intensive care and the management after discharge. CONCLUSION: A multi-disciplinary group of experts achieved consensus on recommendations concerning intensive care for very old patients, which were approved and endorsed by ESICM. The implementation requires a careful analysis of available healthcare resources and should proceed in a stepwise fashion.
Keywords: senioři nad 80 let; Consensus; Geriatrics; Europe; konsensus; Evropa; Emergency medicine; geriatrie; Delphi Technique; péče o pacienty v kritickém stavu; Critical Care; Aged, 80 and over; Geriatric medicine; Humans; Critical care; delfská metoda; Delphi study; Intensive care; lidé